Duration of Perioperative Antibiotic Prophylaxis in Open Fractures: A Systematic Review and Critical Appraisal - Niels Vanvelk; Baixing Chen; Esther M. M. Van Lieshout; Charalampos Zalavras; T. Fintan Moriarty; William T. Obremskey; Michael H. J. Verhofstad; Willem-Jan Metsemakers (MDPI AG, 2022)
Fracture-related infection (FRI) remains a serious complication in open fracture care. Adequate surgical treatment and perioperative antibiotic prophylaxis (PAP) are key factors influencing the outcome. However, data concerning the optimal duration of PAP is scarce. The aim of this systematic review was to provide an overview of current evidence on the association between PAP duration and FRI in open fractures. A comprehensive search on 13 January 2022, in Embase, Medline, Cochrane, Web of Science and Google Scholar revealed six articles. Most studies compared either 1 day versus 5 days of PAP or included a cut-off at 72 h. Although prolonged PAP was not beneficial in the majority of patients, the variety of antibiotic regimens, short follow-up periods and unclear description of outcome parameters were important limitations that were encountered in most studies. This systematic review demonstrates a lack of well-constructed studies investigating the effect of PAP duration on FRI. Based on the available studies, prolonged PAP does not appear to be beneficial in the prevention of FRI in open fractures. However, these results should be interpreted with caution since all included studies had limitations. Future randomized trials are necessary to answer this research question definitively.